1985
DOI: 10.2216/i0031-8884-24-1-35.1
|View full text |Cite
|
Sign up to set email alerts
|

The osmotic role of mannitol in the Phaeophyta: an appraisal

Abstract: 1985) The osmotic role of mannitol in the Phaeophyta: an appraisal. Phycologia 24: 35-47.Natural abundance l3C nuclear magnetic resonance spectroscopy (NMR) has shown mannitol to be the only major low molecular weight organic compound present in osmotically significant amounts within cells of the fo llowing marine brown algae: Alaria esculenta, Ascophyllum nodosum, Ectocarpus siliculosus, Fucus serratus, F. spiralis, F. vesiculosus, Halidrys siliquosa, Laminaria digitata, L. hyperborea, L. saccharina and Pilay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
65
2

Year Published

1986
1986
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(71 citation statements)
references
References 46 publications
4
65
2
Order By: Relevance
“…The reduction of photosynthetic rate for Atlantic E vesiculosus plants in 1.5 and 102 ppt and in higher salinities for Baltic plants demonstrates that salinity does have an effect on photosynthesis. This is contrary to the observations by Reed et al (1985) who found only a minor variation in the photosynthetic rate of F. serratus in the salinity range of 7 to 50 ppt.…”
Section: Mannitolcontrasting
confidence: 99%
See 2 more Smart Citations
“…The reduction of photosynthetic rate for Atlantic E vesiculosus plants in 1.5 and 102 ppt and in higher salinities for Baltic plants demonstrates that salinity does have an effect on photosynthesis. This is contrary to the observations by Reed et al (1985) who found only a minor variation in the photosynthetic rate of F. serratus in the salinity range of 7 to 50 ppt.…”
Section: Mannitolcontrasting
confidence: 99%
“…However, the calculated intracellular water content values appear to give reliable trends between populations. Reed et al (1985) gave values of water partitioning of Atlantic F vesiculosus which are in reasonable agreement with the values from our study. Despite a similar response between the populations it is worth noting that the changes in intracellular water vs salinity are greater in plants from the Baltic than from the Atlantic.…”
Section: Mannitolsupporting
confidence: 90%
See 1 more Smart Citation
“…The only potential osmoregulatory solutes not detected are inorganic ions. Natural abundance 13C NMR has been used to identify the organic osmotica in filamentous fungi (Gadd et al, 1984), cyanobacteria (Reed et al, 1985b), algae (Reed et al, 1985a) and certain Gramnegative (Larsen et al, 1987) and Gram-positive (Hutkins et al, 1987) bacteria. Such use of NMR enables preliminary identification of all major organic solutes which then permits the selection of specific chemical assays or other rapid quantitative techniques for further work, examining the characteristics of accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…The liberation of intracellular low-molecularweight metabolites from hypoosmotically-stressed cells has been demonstrated for several microalgae, including Monochrysis lutheri, which released cyclohexanetetrol (see Hellebust 1974), Platymonas subcordiformis, which released mannitol (Kirst 1977), Phaeodactylum Mcornutum, which liberated proline (Schobert 1980) and the filamentous, colonial bluegreen alga (cyanobacterium) Rivularia atra, which released trehalose (Reed & Stewart 1983). While data exist to show that marine brown macroalgae accumulate the hexitol mannitol as an osmotically-active intracellular solute (see Reed et al 1985a), there is a lack of information on the extracellular liberation of mannitol upon osmotic shock treatment. The present study was carried out to assess the effects of hypoosmotic shock upon mannitol release from plants of the euryhaline brown alga Pilayella littoralis (L.) Kjellm an alga found in estuarine and marine intertidal habitats where rapid changes in salinity may occur.…”
mentioning
confidence: 99%